Can Ecological Momentary Assessments Be Used as Daily Markers of Personality Traits?. (17th December 2021) - Pasquini, Giancarlo; Neubauer, Andreas; Eaton, Nicholas; Clouston, Sean; Graham, Eileen; Mroczek, Daniel; Scott, Stacey
Abstract: This study hypothesized that select ecological momentary assessment (EMA) survey items are sensitive to day-to-day fluctuations in personality traits Extraversion (E) and Neuroticism (N). As part of the Einstein Aging Study, 312 older adults (Mage=76.96 years, SD=4.85 years, range=70-90 years) completed up to 5 EMA surveys per day for 16 days and a Big Five trait personality measure. Parallel two-factor multilevel confirmatory factor analyses were conducted for E (Daily-E; Trait-E) and N (Daily-N; Trait-N). The E model showed good fit (CFI=.95; TLI=.94; RMSEA=.02) and a significant correlation of .20 between Daily-E and Trait-E factors. The N model showed poor fit (CFI=.68; TLI=.61; RMSEA=.06). Results suggest EMA items can be used as daily markers of Extraversion, yet results are unclear for Neuroticism due to poor model fit. Daily markers of Extraversion can be used to detect fluctuations in personality traits across days that may predict long-term personality change.